Analysis of the Influence of Attraction on Interest in Visiting the Indonesia Science Center, Taman Mini Indonesia Indah - Peng, Bryan; Berutu, Feronika (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The Indonesia Science Center is located inside Taman Mini Indonesia Indah in East Jakarta, serves as an interactive science exhibition venue. It offers various exhibits designed to enhance knowledge and understanding of science. This research aims to assess the extent to which attractiveness influences the interest in visiting the Indonesia Science Center at Taman Mini Indonesia Indah. This study adopts a quantitative research methodology, incorporating multiple linear regression analysis, classical assumption tests, hypothesis testing through t-tests and f-tests, and determination coefficient tests, all conducted using SPSS software. The sample comprises 100 respondents, including both individuals who have visited and those who have not visited the Indonesia Science Center at Taman Mini Indonesia Indah, East Jakarta. The research findings indicate that the overall mean score for variable X (Attractiveness) is 4.10, while the overall mean score for variable Y (Interest in Visiting) is 4.11. The t-test results show a significance value of less than 0.001, which is below the 0.05 threshold, indicating that variable X (Attractiveness) significantly affects variable Y (Interest in Visiting). The coefficient of determination (r²) is calculated to be 0.688, suggesting that 68.8% of the variance in variable Y is explained by variable X.